Faktor-faktor yang Mempengaruhi Kejadian Malnutrisi Pasien Dewasa di Ruang Rawat Inap Rumah Sakit - I Gede Agung Kusumayanti; Hamam Hadi; Susetyowati Susetyowati (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2004)
Background : Nutrient intakes may influence nutritional status of patients during health care. It was reported that nutritional status of 75% of hospitalized patients declined during hospitalization.Objective: The objectives of this study was to assess factors that may influence malnutrition among adult patients in hospital.Methods: This study was done using a nested case control study design. Subjects were inpatients of internal and neurology departments of Sanglah, Sardjito and M. Jamil hospitals. They were all given oral feeding, inconsciousness condition, cooperative, and non-ascites. Data on food consumption were obtained using comstock methods, while nutritional status were measured using Subjective Global Assessment.Results: Low energy intake, length of stay, infection, and special diet were all associated with a higher risk of hospital malnutrition. Patients with low energy intakes were 2.4 (OR=2.4, 95%CI= 1.17-4.92) times more likely to be malnourished than those with sufficient energy intakes. Patients with length of stay >= 7 days were 8 (OR=8.15, 95% CI =1.87-35.51) times more likely to be malnourished than those with length of stay < 7 days. Patients with infectious diseases were 3 (OR= 0.33, 95% CI= 0.17-0.64) times less likely to be malnourished than those with non infectious diseases. Lastly, patients with special diet were 2 (OR=1.96, 95% CI= 1.05-3.68) times more likely to be malnourished than those without special diet.Conclusions: Low energy intake, length of stay, non infectious diseases, and special diet are risk factors of malnutrition in adult hospitalized patients.